Pick your poison: the Ripoptosome, a cell death platform regulating apoptosis and necroptosis - Feoktistova, Maria; Geserick, Peter; Panayotova Dimitrova, Diana; Leverkus, Martin (Cell cycle, 2012)
At an unbelievable pace, recent evidence has emerged that demonstrates the importance of a programmed form of necrosis (necroptosis) in physiology, pathophysiology and embryonic development. It is clear that the understanding of the intracellular control of necroptosis as compared to caspase-dependent apoptosis is of paramount importance. Tumorigenesis, immune surveillance of cancer and pathogen-induced disease, to name only a few, appear to be affected by the mode of cell death in vivo. Here, we discuss the Ripoptosome, a newly defined 2 MDa intracellular signalling complex that can be formed upon genotoxic stress or loss of inhibitor-of apoptosis proteins (IAPs). The Ripoptosome is a signaling platform that can switch modes between apoptotic and necroptotic cell death. In this report, we extend our recent studies and further the notion that the stoichiometric balance between RIP1 and cIAPs is critical for Ripoptosome formation. Furthermore, we demonstrate the critical relevance of the balance of expression levels of short (cFLIPS) or viral (vFLIP) forms of FLIP and RIP3 kinase for the spontaneous execution of necroptosis whenever cIAPs are absent in the cells. Our study thus supports and extends the intriguing role of the Ripoptosome for the regulation of apoptosis and necroptosis.
Gesehen am 15.08.2019